Flowcytometric analysis of acute leukemia - Aziz, Muhammad Zaki Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
A review has been made of the 84 paediatric and adult cases of acute leukemia between January 2003 until January 2005. These cases were classified morphologically (using FAB classification) and immunophenotypically. A total of93 paediatric and adult cases were diagnosed, however only 84 records of patients were retrievable from Haematology Lab record books. By F AB classification, 43 cases were classified as Acute Myeloid Leukemia (AML) and 41 cases as Acute Lymphoblastic Leukemia. Acute Leukemia was immunophenotypically classified as AML with 51%, B-ALL (31%), T-ALL (14%), Acute Biphenotypic Leukemia ( 4% ). Contribution of Flow Cytometry analysis to patient is dynamic and evolving with _clinical relevance of biologic parameters and also for the prognostic information. This study was hope to give some benefit in the information which could be used in health area especially in the diagnosed and treatment of acute leukemia